2015
DOI: 10.1093/abbs/gmv095
|View full text |Cite
|
Sign up to set email alerts
|

Critical roles of chemokine receptor CCR5 in regulating glioblastoma proliferation and invasion

Abstract: Glioblastoma (GBM) is the most prevalent malignant primary brain tumor in adults and exhibits a spectrum of aberrantly aggressive phenotype. Tumor cell proliferation and invasion are critically regulated by chemokines and their receptors. Recent studies have shown that the chemokine CCL5 and its receptor CCR5 play important roles in tumor invasion and metastasis. Nonetheless, the roles of the CCR5 in GBM still remain unclear. The present study provides the evidence that the chemokine receptor CCR5 is highly ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 52 publications
1
43
0
Order By: Relevance
“…As shown in Figure 1A, the levels of several cytokines including CX3CL1, RANTES, and CCL11 were upregulated in GBM tumors. Since previous studies had shown that RANTES [15] and CX3CL1 [16] expression were correlated with the development of GBM, we focused on elucidating the role of CCL11. Real-time quantitative PCR demonstrated that CCL11 was overexpressed in 8 freshly collected GBM samples compared with paired adjacent tissue from the same subject (Figure 1B, left panel).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 1A, the levels of several cytokines including CX3CL1, RANTES, and CCL11 were upregulated in GBM tumors. Since previous studies had shown that RANTES [15] and CX3CL1 [16] expression were correlated with the development of GBM, we focused on elucidating the role of CCL11. Real-time quantitative PCR demonstrated that CCL11 was overexpressed in 8 freshly collected GBM samples compared with paired adjacent tissue from the same subject (Figure 1B, left panel).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that several chemokines and their receptors including CXCL12 [21], CXCL8 [22], CCL2 [23], RANTES [15], CX3CL1 [16], CCR4 [24], CXCR4 [25] and CX3CR1 [26] participate in tumorigenesis. In particular, CCR2 [27], CCR3 [16], and CCR5 [16, 28], three known CCL11 receptors, were all markedly upregulated in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…However, while CCL5 function in glioma has not been fully elucidated, several reports have suggested that it might be an important chemokine in this setting. First, one of the main CCL5 receptors, CCR5, is expressed in U87 and U251 glioblastoma cell lines, such that its knockdown inhibits U87 growth in nude mice [35]. Second, CCL5 mRNA and protein expression are elevated in both tumor tissue and serum from patients with high-grade glioma [36].…”
Section: Discussionmentioning
confidence: 99%
“…The axis of chemokines and chemokine receptors has been demonstrated as important regulators in the invasion and metastasis process of cancer cells. CCR5, whose ligands include CCL3 (MIP-1Îą), CCL4 (MIP-1β) and CCL5 (RANTES), was reported to be highly expressed in GBM tissue (24,25). A recent study showed that the overexpression of CCR5 was associated with poor prognosis of GBM patients, and activation of CCR5 signaling promoted the invasion of u87 and u251 cell lines in vitro by upregulating MMP-9 expression (24).…”
Section: Discussionmentioning
confidence: 99%